SYNTHESIS OF THALLIUM SULPHATE IN A SULFURIC ACID SOLUTION AT POLARIZATION BY CURRENT - A. B. Baeshov; E. Zh. Tuleshova; G.T. Sarbayeva; M. A. Ozler; M.T. Sarbayeva (Academic Scientific Journal of Chemistry, 2021)
Nowadays, the one of the actual problems is the recycling of metal waste and its provision to consumers. However, it is known that there are a number of difficulties with the recycling of thallium waste. By using new recycling methods, it’s possible to increase thallium resources and lower prices for thallium-derived products. Therefore, some work was carried out to extract its compounds from thallium waste by studying the electrochemical properties of thallium in our research work. The experimental results showed that thallium electrodes dissolve in an aqueous solution of sulfuric acid under alternating current polarization with the formation of thallium (I) sulfate. In this work, the kinetics of electrochemical oxidation-reduction of thallium in aqueous solutions of sulfuric acid is studied by potentiometry. To characterize the mechanism of thallium electrooxidation, the following parameters were calculated: the order of the reaction and the effective activation energy of the process. The impact of electrolysis modes: current density, concentration and temperature of the electrolyte on the dimensional characteristics of the obtained thallium (I) sulfate was investigated